PENGARUH IMPOR BERAS ASAL THAILAND DAN VIETNAM TERHADAP KESTABILAN HARGA BERAS DI INDONESIA - Fadillah Juliashar; Khansa Tatimah; Nur Aqilah Salma Abiyyah; Rinandita Wikansari (AGRORADIX : Jurnal Ilmu Pertanian, 2024)
This research aims aims to analyze the impact of rice imports from Thailand and Vietnam on rice market price stability in Indonesia. Using quantitative methods, this study explores time series data from 2018 to 2022 to analyze demand and supply. Average rice consumption, domestic production, and rice imports from both countries are calculated as part of the quantitative calculations. An evaluation of medium and premium rice price variables was also conducted to identify potential market fluctuations. The research findings provide in-depth insights into the relationship between rice imports, domestic production, and rice price stability in Indonesia. This research is expected to make a valuable contribution in managing rice supply and formulating appropriate economic policies in Indonesia. The research was conducted to determine whether production, price and consumption have a relationship with Indonesia's rice imports. From various sources by discussing the production, price and level of domestic consumption. It was found that Indonesia's rice import quantity is influenced by the level of domestic rice consumption and production, which has an impact on the price of rice in the Indonesian market.